Effect of Hydrocarbon Presence and Properties on the Magnetic Signature of the Reservoir Sediments of the Catcher Area Development Region, UK North Sea - Abdulkarim, Maryam A.; Muxworthy, Adrian R.; Fraser, Alastair; Sims, Michael; Cowan, Alison (Frontiers in Earth Science, 2022)
This paper presents a detailed study investigating the effect of hydrocarbon presence on magnetic mineral diagenesis in sediments from the Catcher Area Development (CAD) region, UK North Sea, between 1000 – 1500 m (True Vertical Depth Sub-Sea). Magnetic analysis of core samples from hydrocarbon fields of the region and nearby dry-well sandstones (background) was carried out to determine if their signatures can serve as a proxy for understanding petroleum reservoir systems. From the background samples, nanometric and micron-sized magnetite, hematite and titano-iron oxides, were identified. Hydrocarbon presence in the reservoir sediments was found to diminish the iron-oxide signature and favour the precipitation of hexagonal pyrrhotite, siderite and potentially vivianite, lepidocrocite, greigite and paramagnetic iron sulphides. Hexagonal pyrrhotite was found at the oil-water transition zones. This relationship is possibly related to biodegradation at this interface. Siderite was found in increased abundance at shallower depths within the reservoir, which we attribute to hydrocarbon vertical migration and biodegradation. The interbedded shales also experienced significant magnetic mineral diagenesis that depended on its proximity to the hydrocarbon plume. These findings suggest that mineral magnetism can be applied to the identification of oil-water transition zones, reserve estimation, production planning and the determination of hydrocarbon migration pathways. It also suggests that mineral magnetic methods can be used to estimate the timing of hydrocarbon migration.